Potential therapeutic effects of branched-chain amino acids supplementation on resistance exercise based muscle damage in humans - da Luz, C. R.; Nicastro, H.; Zanchi, N. E.; Chaves, D. F. S.; Lancha Jr, A. H. (Journal of the International Society of Sports Nutrition, 2011)
Branched-chain amino acids (BCAA) supplementation has been considered an interesting nutritional strategy to improve skeletal muscle protein turnover in several conditions. In this context, there is evidence that resistance exercise (RE)-derived biochemical markers of muscle soreness (creatine kinase (CK), aldolase, myoglobin), soreness, and functional strength may be modulated by BCAA supplementation in order to favor of muscle adaptation. However, few studies have investigated such effects in well-controlled conditions in humans. Therefore, the aim of this short report is to describe the potential therapeutic effects of BCAA supplementation on RE-based muscle damage in humans. The main point is that BCAA supplementation may decrease some biochemical markers related with muscle soreness but this does not necessarily reflect on muscle functionality.